Assertiveness Training Format Kelompok Dalam Pelayanan Konseling - Lubis, Khadijah; Hayati, Ria; Novirson, Rizki (JURNAL KONSELING GUSJIGANG, 2022)
Counseling services that are effective and on target are needed by counselors. Ideally, counselors should have insight, and skills in implementing creative and innovative counseling techniques. There are still counselors who have minimal knowledge and skills regarding counseling techniques. One of them is the assertiveness training technique in the group format, which is one of the recommended behavior counseling techniques to improve individual interpersonal competence. The steps for implementing assertiveness training are (1) rational strategy, (2) identification of situations that cause problems, (3) exploration, (4) role-playing, giving feedback, and better behavioral models. (5) carry out exercises and practice, (6) repeat the exercises, (7) do homework and follow-up, and (8) terminate. This implementation shows that group format assertiveness training can be implemented in counseling services to alleviate problems and improve individual interpersonal skills. Therefore, counselors are expected to improve their skills and apply group format assertiveness training in counseling services.